Optimizing energy and CO2 efficiency in last-mile delivery using hybrid fleet models - Armin Mahmoodi; Leila Hashemi; Jeremy Laliberte; Seyed Mojtaba Sajadi (Sustainable Futures)
Effective urban delivery systems demand innovative approaches to reduce energy use and lower CO2. This study compares the environmental performance of hybrid and diesel trucks with quadcopter and fixed-wing remotely piloted aircraft systems (RPAS), employing a multi-objective optimization approach non-dominated sorting genetic algorithm II (NSGA-II) to identify optimal delivery routes balancing operational efficiency and sustainability. Given that existing solutions like e-bikes or electric vans may not be feasible everywhere, this research evaluates different vehicle types under various urban delivery scenarios. Using a synthetic dataset that simulates realistic conditions, the findings reveal that fixed-wing RPAS excel in long-range efficiency, while quadcopters perform better in short-range deliveries. Hybrid trucks are advantageous for larger loads, reducing emissions compared to diesel trucks. The results highlight key trade-offs in energy use and emissions, advocating for a mixed-fleet strategy tailored to specific logistics needs. This study provides actionable insights for sustainable urban freight planning and policymaking.